LIMBAH TEPUNG BATANG KANGKUNG (Ipomea aquatica) SEBAGAI BAHAN BAKU PAKAN IKAN NILA (Oreochromis nilotikus) DI KARAMBA - Marthen, Sonny H.; Lumenta, Cyska (EUGENIA, 2006)
This research was carried out at spp (Sekolah Pertanian Pembangunan) Manado Kalasey. The fishwere reared in karamba (9 units) each units contained 50 fish, 14-16 weight. The experiment will be tested using completely random design using 3 deffierent treatment. One treatment is using comercial pellet and two treatmens all using pellets added with and swampcabbage stalk flour 20% and 30 %, each treatment hare 3 replicateries. Feeding frecuenci was 3 times a day and feeding rate was 5 % of their body weight the growth was observed every two weeks. The result analysis from 3 treatment show that the relative growth of treatment A was (312.67%) B was (282.79%), and C (262.41%). The was effisincy feeding foor treatment A was hare (49.43%), B was 48.78% and C was 47.26Â  5% Where as nutient conversion rate A was are (0%), B was 3.47% and C was (3.82%).Keywords: Swamp cabbage stalk flow (Ipomea aquatica) Nila gif, karamba